Obstacles to using learning platforms during the COVID-19 pandemic from the point of view of primary school teachers in Riyadh - Al-Shaibani, Noura Ghazi; Al-Hussein, Ahmed Mohammed (Journal of Curriculum and Teaching Methodology, 2024)
The objective of the study was to identify the challenges encountered by primary school teachers in Riyadh when utilizing learning platforms during the COVID-19 pandemic. Additionally, it aimed to determine if there were variations in identifying these obstacles based on gender, academic qualifications, or experience levels. The study relied upon a descriptive survey approach. The study population consisted of all primary school teachers in public schools in Riyadh, reaching 19,457 persons, while the studied sample amounted to 559 teachers-both males and females- selected in a simple random way. The questionnaire, used as a tool to collect data on obstacles to use learning platforms during the COVID-19 pandemic, was analyzed by utilizing the Statistical Package for Social Sciences (SPSS) software. The study concluded with the following results: The degree level of obstacles for all study axes came with a high uniformity, whereas the obstacles related to parents came in the first place, followed by the technical obstacles, while the obstacles related to the learner came in the third place, and the obstacles related to the teacher was in the fourth place. Ultimately, the obstacles related to school administration came in fifth place. There are no statistically significant differences between the sample responses regarding obstacles of encountering the learning platforms according to the variables of gender, academic qualification, and years of experience. The study culminated with many recommendations, the most predominant of which are: Supporting parents and qualifying them for the distance education process by providing them with the skills, knowledge and tools that enable them to know their real roles in the educational process. And providing the necessary infrastructure for the application of distance education.
Keywords: Obstacles; Learning platforms; COVID-19 pandemic; Primary school